A Stable Polyoxometalate‐Pillared Metal–Organic Framework for Proton‐Conducting and Colorimetric Biosensing. Issue 33 (14th July 2015) - Zhou, En‐Long; Qin, Chao; Huang, Peng; Wang, Xin‐Long; Chen, Wei‐Chao; Shao, Kui‐Zhan; Su, Zhong‐Min
Abstract A stable metal–organic framework pillared by Keggin‐type polyoxometalate, Cu6(Trz)10(H2O)4[H2SiW12O40]⋅8 H2O (Trz=1, 2, 4‐triazole) (1), has been prepared under hydrothermal condition. The 2D layer structure with a 22‐member ring was formed by Cu2+ ions, which are connected with each other via the Trz ligands on the ab plane. Thus, the 2D layers are further interconnected through Keggin polyoxoanions to generate a 3D porous network with a small 1D channel. Moreover, the presence of polyoxoanions make it exhibit selective adsorption of water and proton‐conducting properties. Additionally it showed efficient intrinsic peroxidase‐like activity, providing a simple and sensitive colorimetric assay to detect H2O2.